Bone marrow stem cells and liver regeneration - Almeida-Porada, Graça (2010)
The development of new approaches to treat patients with hepatic diseases that can eliminate the need for liver transplantation is imperative. The use of cell therapy as a means of repopulating the liver has several advantages over whole organ transplantation, since it would be less invasive, less immunogenic, and would allow the use, in some instances, of autologous-derived cells. Stem/progenitor cells that would be ideal for liver repopulation would need to have characteristics such as availability and ease of isolation, the ability to be expanded in vitro, ensuring adequate numbers of cells, susceptibility to modification by viral vector transduction/genetic recombination, to correct any underlying genetic defects, and the ability of restoring liver function following transplantation. Bone marrow-derived stem cells such as Hematopoietic, Mesenchymal and Endothelial Progenitor cells possess some or most of these characteristics, making them ideal candidates for liver regenerative therapies. Here, we will summarize the ability of each of these stem cell populations to give rise to functional hepatic elements which could mediate repair in patients with liver damage/disease.